Hepatotoxicity by tamsulosin / dutasteride: report of a probable case - Yance, Stalin (2023)
Tamsulosin and dutasteride are drugs widely used to treat benign prostatic hypertrophy. having a good safety profile. There are few reports of liver injury associated with the use of tamsulosin; however, there are no reports of hepatic toxicity from the use of dutasteride and the combined use of tamsulosin/dutasteride. We present the case of a 64-year-old man who developed liver injury after the combined use of tamsulosin/dutasteride, developing a pattern of hepatocellular damage and acute hepatitis symptoms. Viral, autoimmune, and metabolic storage diseases of the liver were ruled out, as well as biliary pathology by means of abdominal ultrasound and resonance cholangiography. In the causality evaluation, CIOMS-RUCAM presented: 6 points (probable) and Naranjo: 4 points (possible). The patient presented a clinical and laboratory response after discontinuing the drug.